Les amphores africaines dans la région toulousaine aux iie et ier s. av. n. è. - Laurence Benquet; Claudio Capelli (Antiquités Africaines, 2017)
This paper presents a synthesis on African amphorae identified in the Toulouse area at the end of the Iron Age. Thanks to recent discoveries from rescue excavations, a chronological analysis of the quantitative evolution of these imports is offered. Petrographic analyses complement this study.